Efficacy and safety of local anesthetics bupivacaine, ropivacaine and levobupivacaine in combination with sufentanil in epidural anesthesia for labor and delivery: a meta-analysis. (November 2014) - Lv, Bao-sheng; Wang, Wei; Wang, Zhuo-qiang; Wang, Xian-wang; Wang, Jing-hua; Fang, Fang; Mi, Wei-dong
Abstract Background: In epidural analgesia, synthetic opioids increase the potency of amide local anesthetics by modifying their analgesic properties. The purpose of this systematic review and meta-analysis is to compare the efficacy and safety of bupivacaine with ropivacaine and levobupivacaine in combination with sufentanil (BUPI-, ROPI-, and LBUPI-SUF respectively) in epidural analgesia for labor. Methods: A literature search was made in multiple electronic databases for original research papers published between 1995 and 2014. Meta-analyses were based on mean differences between the groups as well as odds ratios where appropriate. Both the fixed effects and random effects models were utilized and heterogeneity was tested with the I2 index. Results: Analgesia duration was significantly longer in ROPI-SUF and LBUPI-SUF than in BUPI-SUF administered women with a mean difference (95% CI) of 16.12 (2.56, 29.68); P < 0.03 and 18.02 (9.09, 26.96); P < 0.0001 respectively under a random effects model (REM). Effective analgesia achievement was significantly earlier in the BUPI-SUF than in either the ROPI-SUF (2.61 [1.87, 3.36]; P < 0.00001) or the LBUPI-SUF groups (4.53 [3.66, 5.40]; P < 0.00001) under a fixed effects model (FEM) but not under a REM (I2 = 85%). Motor blockade incidence was higher in BUPI-SUF anesthetized patients, although the difference was not statistically significant. A higher incidence of instrumental deliveries was evident in the ROPI-SUF (FEM: 1.68 [1.13, 2.50]; P < 0.02/REM: 1.76 [1.00, 3.11]; P = 0.05) and LBUPI-SUF (FEM: 2.03 [1.07, 3.86]; P < 0.04/REM: 2.03 [1.07, 3.86]; P < 0.04) groups than in the BUPI-SUF group of patients. Inconsistencies in the availability of parametric data and use of slightly varying anesthetic dosages in included studies were important limitations. Conclusion: Whereas significantly longer labor analgesia can be achieved with ROPI-SUF and LBUPI-SUF and ropivacaine is associated with comparatively less motor blockade, labor duration after epidural analgesia has been found to be shorter in BUPI-SUF and there is a low incidence of instrumental delivery.